Impact of temperature severity on hydrothermal carbonization: Fuel properties, kinetic and thermodynamic parameters - Nawaz A.; Kumar P. (My University, 2025)
The current study intended to explore the impact of hydrothermal carbonization temperature (180, 230, and 280 °C) on the fuel properties, kinetics, thermodynamics, and reaction mechanism of sunflower stalks (SS). Hydrochars obtained at different temperatures were pyrolyzed in a TGA (Thermogravimetric analyzer) at three distinct heating rates. The impact on functional groups, surface morphology, and crystallinity were examined based on the characterization methods such as FTIR, FE-SEM, and XRD. The kinetic parameters were estimated based on the isoconversional methods of Kissinger Akahira Sunose (KAS), Ozawa Flynn Wall (OFW), and Vyazovkin (VZK), whereas the reaction mechanism was deduced employing Z(α) master plot method. The mean value of activation energy obtained for the raw-SS, SS-180, SS-230, and SS-280 was (188.71, 189.06, and 176.4 kJ/mol), (165.6, 167.33, and 155.54 kJ/mol), (219.77, 218.78, and 206.83 kJ/mol), and (299.37, 296.6, and 281.02 kJ/mol) based on KAS, OFW, and VZK method, respectively. The findings of the current study can be used to develop and design pyrolysis reactors for clean biofuel generation from SS. © 2022 Elsevier Ltd